Muslim Community Dramaturgy Through Ritual Cross-Religious in Moluccas, Indonesia - Ridwan, M.; Sulaeman, Sulaeman; Hadawiah, Hadawiah; Darma, Darma; Tetulau, Muhammad (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
On December 2, 2018, Immanuel Church of GPM Amahusu Klasis in Moluccas, Indonesia, hosted a cross-religious ritual involving the Muslim and Christian communities. The "worship orang basudara" (worship of brothers) ritual took place during the first advent week, with participation from Tial Village and Laha Village (Muslim community) and Amahusu Village and Hatalai Village (Christian community). The ritual incorporated religious symbols such as the call to prayer, recitation of the Rawi Barzani, lighting one of four candles, and singing hymns. This article examines how the social interaction process manages the frontstage and backstage impressions displayed by the Muslim community after participating in the ritual. Data were collected from fifteen individuals through participant observation and interviews, using a qualitative approach based on a subjective interpretive paradigm from a dramaturgical perspective. The findings reveal that the Muslim community involved in the ritual manages impressions through self-repentance, supplication to Allah SWT, and mutual acceptance with the Christian community in social contexts. After the ritual, the Muslim community engages in frontstage social interactions with fellow involved Muslims, non-involved families (negation families), non-involved communities (exclusion communities), religious organisations, and government institutions. Backstage actions include self-introspection (self-evaluation of engagement), repentance (admission of guilt), and prayer (asking for help). This article contributes to understanding the subjective experiences of Muslim communities following ritual involvement, particularly in managing backstage impressions. It suggests that Muslim-Christian communities can overcome disharmony through mutual acceptance of religious differences, promoting peace through contemporary human values.